DEVELOPING HALAL COMPLIANCE CRITICAL POINTS (H CCP) FOR HALAL SLAUGHTERING SYSTEM - H. Jalil; T. Qamar (Journal of Animal and Plant Sciences, 2019)
The Quranic concept of Halal-un-Tayyab assures the compliance of food safety measures together with the consumption of lawful food. The concept of Halal food without the inclusion of Tayyab (pure and safe) is lacking with the comprehensiveness of the Quranic concept of Halal- un- Tayyab. This paper is an effort to develop certain parameters called ‘Halal Compliance Critical Points (HCCP)' in the light of the guidance of the Holy Quran and Sharia for Halal slaughtering & processing system. The paper also aims to explore whether and to what extent food safety is a part of the Halal and Tayyab concept and how that is currently backed up by the Halal food sector in the Muslim and non-Muslim countries. Since Tayyab sets the general principle for assuring food safety in the Halal sector, it is apparent that Halal food chain should comply with both Halal fundamental and food safety requirements. In order to ensure the compliance of Sharia procedures for Halal-un-Tayyab system, attempt has been made to develop procedure for Halal Compliance Critical Points (HCCP). This research based HCCP system would help formalize the credible Halal certification and audit system in the interest of Halal industry and the satisfaction of Halal consumers.
Keywords: Compliance; Food Safety; Halal; HCCP; Sharia; Tayyab